The Determination of Antithrombin III - Bounameaux, H; Duckert, F; Walter, M; Bounameaux, Y (Thrombosis and Haemostasis, 1978)
At III levels were measured with six methods in 36 people: 10 healthy controls, 10 women taking a progestagen Lynestrenol and 16 women taking a combined oestrogen-progestagen contraceptive pill.The reproducibility and the sensitivity of these methods as well as the correlation between methods were studied.The Hensen and Loeliger technique had a poor reproducibility and the results obtained with the Howie technique were not in good correlation with those obtained with the other methods, especially in the group taking oral contraceptives. The two amidolytic methods using chromogenic substrates were found to be very accurate for antithrombin III activity determination. The rocket Immunoelectrophoresis was more accurate and more practical than the radial immunodiffusion.With all methods - except the one of Howie–the 10 women taking progestagen Lynestrenol and the 16 taking combined oestrogen-progestagen had a low AT III and differed significantly from the 10 normals tested. No difference was observed between women taking progestagen only or an oestrogen-progestagen combination.